Spermatological characters of bothriocephalideans (Cestoda) inferred from an ultrastructural study on Oncodiscus sauridae and Senga sp. - Šípková, Lenka (Jihočeská univerzita, 2011)
Spermiogenesis and ultrastructure of the spermatozoon of two bothriocephalidean cestodes, Oncodiscus sauridae and Senga sp., have been studied using transmission electron microscopy. The presence of a classical pattern for spermatological characters (spermiogenesis of type I with dense-material in early stages and sperm of type II with a characteristic ring of cortical microtubules in the anterior part) in Bothriocephalidea is discussed.
Spermatological characters of bothriocephalideans (Cestoda) inferred from an ultrastructural study on Oncodiscus sauridae and Senga sp.
Keywords: bothriocephalidea; cestode; spermatozoon; spermiogenesis; transmission electron microscopy